(untitled) (European Journal of Pure and Applied Mathematics, 2025)
A nonlinear Langevin fractional system involving two ψ-Caputo derivatives with random effects is investigated. First, a random version of Perov’s fixed-point theorem in generalized Banach space endowed with the Bielecki-type vector-valued norm is employed to achieve a uniqueness result. Second, the existence result is established using Sadovskii’s fixed point principle under fairly general conditions on the nonlinear forcing terms. Finally, our findings are justified through illustrative examples.